2016
DOI: 10.1021/acs.jmedchem.6b00821
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent Acyclic, Tripeptidic, Acyl Sulfonamide Inhibitor of Hepatitis C Virus NS3 Protease as a Back-up to Asunaprevir with the Potential for Once-Daily Dosing

Abstract: The discovery of a back-up to the hepatitis C virus NS3 protease inhibitor asunaprevir (2) is described. The objective of this work was the identification of a drug with antiviral properties and toxicology parameters similar to 2, but with a preclinical pharmacokinetic (PK) profile that was predictive of once-daily dosing. Critical to this discovery process was the employment of an ex vivo cardiovascular (CV) model which served to identify compounds that, like 2, were free of the CV liabilities that resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The S4 pocket is mostly nonpolar and can accommodate both hydrophobic and hydrophilic side chains in natural HCV substrates (40). However, prior structure-activity relationship (SAR) studies on macrocyclic and peptidic scaffolds show that hydrophobic moieties are associated with higher potencies (41)(42)(43)(44)(45)(46)(47)(48). Thus, the inhibitors designed using molecular modeling had hydrophobic P4 moieties extending into the S4 pocket toward D168.…”
Section: Resultsmentioning
confidence: 99%
“…The S4 pocket is mostly nonpolar and can accommodate both hydrophobic and hydrophilic side chains in natural HCV substrates (40). However, prior structure-activity relationship (SAR) studies on macrocyclic and peptidic scaffolds show that hydrophobic moieties are associated with higher potencies (41)(42)(43)(44)(45)(46)(47)(48). Thus, the inhibitors designed using molecular modeling had hydrophobic P4 moieties extending into the S4 pocket toward D168.…”
Section: Resultsmentioning
confidence: 99%
“…Next we explored a sulfoxide–magnesium exchange–Negishi cross‐coupling protocol to form (hetero)aryl cyclopropanes which are important pharmacophores. [12c] There are no prior examples of cross‐coupling between aryl halides and cyclopropyl organometallics derived from cyclopropyl sulfoxides. [21c] We employed a protocol similar to that which we recently reported for aziridine sulfoxides,[22e] and were delighted to observe the successful Negishi cross‐coupling from both trans and cis ‐cyclopropane derivatives with aryl bromides (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The cyclopropane motif is highly significant in drug discovery as the 10 th most frequently found ring system in small molecule drugs , . It is also present in a variety of biologically active natural products and other medicinally‐important molecules (Figure ) , . Substituted cyclopropanes present a well‐defined 3‐dimensional shape, conformational rigidity, and electronic properties in between that of an alkene and a gem ‐dimethyl group, for example, as a result of the small strained ring structure.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of cyclopropyl-acyl sulfonamide showed 50-fold increase in biochemical potency and a >100-fold increase in cell-based/ replicon potency. However, BMS-605339 (5) was discontinued from clinical trials due to its cardiovascular side effects, but a new compound, BMS-890068 (6), discovered by Sun et al [26] was found to have better antiviral and pharmacokinetic properties.…”
Section: Acyl Sulfonamide P1ʹ Interaction (Bms-605339)mentioning
confidence: 99%